Pretreatment resistance mutations and treatment outcomes in adults living with HIV-1: a cohort study in urban Malawi - Neuhann, Florian; de Forest, A; Heger, E.; Nhlema, A.; Scheller, C.; Kaiser, R.; Steffen, H. M.; Tweya, H.; Fätkenheuer, G.; Phiri, S. (AIDS research and therapy, 2020)
Pre-treatment drug resistance (PDR) among antiretroviral drug-naïve people living with HIV (PLHIV) represents an important indicator for the risk of treatment failure and the spread of drug resistant HIV variants. We assessed the prevalence of PDR and treatment outcomes among adults living with HIV-1 in Lilongwe, Malawi.
Gesehen am 31.03.2021